Tissue-Advanced Glycation End Product Concentration in Dialysis Patients - McIntyre, Natasha J. (American Society of Nephrology, 2010)
Background and objectives: Tissue-advanced glycation end products (AGE) are a measure of cumulative metabolic stress. Assessment of tissue AGE by skin autofluoresence (AF) correlates well with cardiovascular outcomes in hemodialysis (HD) patients. This study aimed to measure and compare tissue AGE levels in HD and peritoneal dialysis (PD) patients and to evaluate the impact of systemic PD glucose exposure. Design, setting, participants, & measurements: Tissue AGE were measured in 115 established dialysis patients (62 HD and 53 PD) using a cutaneous AF device (AGE Reader; DiagnOptics). Values were compared with an age-matched non–chronic kidney disease database. Review of all previous PD solution delivery/prescription data determined PD glucose exposure. Results: PD patients were similar in age to HD patients but had a shorter dialysis vintage. There were no differences in ischemic heart disease or smoking history, statin or angiotensin-converting enzyme inhibitor (ACEi) use, lipids, biochemistry, or prevalence of diabetes. More than 90% of both groups had met current dialysis adequacy targets. Skin AF values in PD and HD patients were similar and strongly correlated with historical PD glucose exposure. Skin AF correlated with age in both groups but with dialysis vintage only in PD patients Conclusions: Cumulative metabolic stress and transient hyperglycemia results in grossly elevated levels of tissue AGE in dialysis patients. In PD patients, this high level of AGE deposition is associated with historical glucose exposure. This observation provides a previously unappreciated potential link between PD exposure to glucose and systemic cardiovascular disease.